Tomato cultivars under different planting dates at the São Gonçalo irrigated perimeter - Cordeiro, Gilberto Gomes; Garri, Arturo C.R. Carvajal; Barreto, Aurelir Nobre; Oliveira, Carlos Alberto V. de; Morais, Gilberto José de (Pesquisa Agropecuaria Brasileira, 2014)
In order to obtain reliable information on the most suitable planting dates and phenological development of four tomato cultivars (Lycopersicon esculentum L.), Rossol, IPA 1, IPA 2, and IPA 3, some trials were set on the alluvial soils of the experimental station of the São Gonçalo irrigated perimeter at Souza, PB, Brazil. The field work was initiated on January 1981 and finished on May 1982. The mentioned trials were installed progressively one each month, and the necessary information was collected to evaluate for each cultivar and for different planting dates the following parameters: productivity, blossom end-rot incidence, mean weight of fruits, and pest and disease incidence. There was no yield difference among the cultivars within the different planting dates. The best planting dates found out were February through May. The lowest yields were obtained when planting on September through January.